Privacy Enhancing Techniques - De Moor, G. J. E.; Claerhout, B.; De Meyer, F. (Methods of Information in Medicine, 2003)
Objectives: To introduce some of the privacy protection problems related to genomics based medicine and to highlight the relevance of Trusted Third Parties (TTPs) and of Privacy Enhancing Techniques (PETs) in the restricted context of clinical research and statistics.Methods: Practical approaches based on two different pseudonymisation models, both for batch and interactive data collection and exchange, are described and analysed.Results and Conclusions: The growing need of managing both clinical and genetic data raises important legal and ethical challenges. Protecting human rights in the realm of privacy, while optimising research potential and other statistical activities is a challenge that can easily be overcome with the assistance of a trust service provider offering advanced privacy enabling/enhancing solutions. As such, the use of pseudonymisation and other innovative Privacy Enhancing Techniques can unlock valuable data sources.
Keywords: Genomic medicine; privacy; confidentiality; stigmatization; discrimination; TTPs; PETs; pseudonymisation